INTRAOCULAR LENS EXCHANGE PROCEDURE AS A MANAGEMENT FOR INTRAOCULAR LENS DISCOLORATION: Poster Presentation - Case Report - Resident - Budiman; Arrizasyifaa, Raden Muhammad Tanri; Sugiarti, Emmy Dwi; Tjokrovonco, Ludwig M.; Knoch, Andrew MH. (Majalah Oftalmologi Indonesia, 2023)
Introduction : Intraocular lens (IOL) discoloration is a rare complication of cataract surgery. It may result in severe visual function impairment and potentially lower the patient's quality of life. IOL exchange is an unusual procedure as the incidence rate was 2 per 1000 surgeries over 8 years. It is the surgical procedure of choice for symptomatic IOL discoloration. Case Illustration : A 50-year-old man came to the hospital complaining of a right eye blurry vision for the previous two months. His right eye had undergone cataract surgery seven years earlier. After having cataract surgery, the patient's vision was clear, but five years later, it began to feel blurry and glare. The patient has a history of well-controlled type II diabetes and hypertension. An intraocular lens discoloration was discovered after a careful examination of the eye (figure 1). For his right eye, the patient underwent an IOL exchange procedure (figure 2). A square-edge single-piece foldable IOL was obtained from the surgery. Follow-up examinations after surgery revealed an improved visual function and a clear intraocular lens (figure 3). Discussion : IOL discoloration may occur years after surgery. It is related to the type of IOL, local ocular factors, and the patient's systemic condition. The IOL exchange procedure consists of IOL extraction and secondary IOL implantation. The extraction can be done by cutting, splitting (bisecting), or folding the IOL. Different methods of fixation can be used for secondary IOL implantation. Conclusion : The IOL exchange procedure can optimally restore visual functions after a severe decline caused by IOL discoloration.